2013
DOI: 10.1007/s13277-013-0803-2
|View full text |Cite
|
Sign up to set email alerts
|

TF/FVIIa/PAR2 promotes cell proliferation and migration via PKCα and ERK-dependent c-Jun/AP-1 pathway in colon cancer cell line SW620

Abstract: Our previous study has demonstrated that tissue factor-factor VIIa (TF/FVIIa) complex promotes the proliferation and migration of colon cancer cell line SW620 through the activation of protease-activated receptor 2 (PAR2). In the current study, the underlying molecular mechanisms of TF/FVIIa/PAR2 signaling in SW620 cells were further explored, with the focus on the role of activator protein-1 (AP-1) subunit c-Jun. The results revealed that PAR2-AP and FVIIa could upregulate c-Jun expression and c-Jun phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 30 publications
2
47
0
Order By: Relevance
“…Both TF isoforms play essential and often isoformspecific roles in cancer biology and pathophysiology, i.e., in cancer-related thrombogenicity, metastasis, and angiogenesis (2,8,21,23,30 ). Differential TF isoform functions are suggested to be mediated by isoformspecific signal transduction via PAR-2 or integrins ␣v␤3, respectively (13,23,24 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both TF isoforms play essential and often isoformspecific roles in cancer biology and pathophysiology, i.e., in cancer-related thrombogenicity, metastasis, and angiogenesis (2,8,21,23,30 ). Differential TF isoform functions are suggested to be mediated by isoformspecific signal transduction via PAR-2 or integrins ␣v␤3, respectively (13,23,24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Differential TF isoform functions are suggested to be mediated by isoformspecific signal transduction via PAR-2 or integrins ␣v␤3, respectively (13,23,24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TF has become one of the targets of targeted therapy for breast cancer cells (Cole et al, 2013), and is considered an important aspect of breast cancer research (Santos et al, 2013). Studies have shown that TF and MMP -9 expression is significantly correlated with breast cancer cells in humans and dogs (Zhao et al, 2008;Hu et al, 2013). In human colon cancer cells Wu et al, 2013a;Wu et al, 2013b), TF promotes the invasion and metastasis of tumor cells by upregulating MMP-9 .…”
Section: Discussionmentioning
confidence: 99%